THE IMPACT OF AN IRREGULAR DAILY ROUTINE ON STUDENTS’ HEALTH - Yuldasheva F. U.; Atkhamova S. U.; Bazuova M. A.; Karimov M. A.; Kalkhorazova Kh. A. (The Conference Hub, 2025)
A proper daily routine is the foundation of every individual’s physical and mental health, as well as their success in life. During the student years, it is especially important to establish a healthy and well-organized daily schedule.An irregular daily routine can have a serious negative impact on students’ lives.